Impact of the Psychological Testing Assessment System (SATEPSI) for Scientific Publications in Psychological Assessment - Mansur-Alves,Marcela (2016)
Abstract The strengthening of psychological assessment in Brazil in the twenty-first century can be understood as a result of the foundation of Psychological Test Evaluation System (SATEPSI, its Portuguese acronym) by Resolution 02/2003 of the Federal Council of Psychology. In this sense, the present study aimed to describe the impact of SATEPSI for research in the area. A survey of Brazilian researchers' publications was conducted in two periods in SciELO and BVS-Psi databases - 1993-2002 and 2003-2014 - using the terms "psychological evaluation", "psychological tests" and "construction / adaptation of psychological instruments". Overall, the results point to the positive impact of SATEPSI for the area of psychological assessment. It was observed an increasing in quantity and quality of publications, as well as a greater variety of psychological tests used in different contexts. It can be concluded that the pursued goals of the Resolution 02/2003 were mostly achieved.